Molluscicidal activity of Sandoricum koetjape plant extract against Oncomelania quadrasi - Amora, Silvin Ezra S.
Schistosomiasis, a parasitic disease that causes chronic disorders has been a major threat to families in 28 provinces in the Philippines including Leyte and Samar. Only niclosamide, a chemical molluscicide was approved by the World Health Organization as a control measure in preventing the spread of the disease but it has it side effects as it is toxic to fish. The search of a plant molluscicide is highly recommended for ecological reasons. A screening of 5 local plant extracts: Sandoricum koetjape, Terminalia catappa, Nauclea orientalis, Plumeria acuminate, Mussaenda philippics was done and S. koetjape showed the highest toxicity with 30% mortality in 50 mg/L and 70% mortality in 100 mg/L. The study was further conducted to test the potential of S. koetjape as molluscicide against Oncomelania quadrate. The standard WHO Immersion Method was adapted and the data were analyzed using Probit analysis and One-Way ANOVA. The results showed that in concentrations 50, 100 and 200 mg/L elicited mortality of 6.7%, 68.9%, 93.3%, respectively, which showed noticeable toxic activity. The plant extract has an LC50 value of 93.3 mg/L and LC90 value of 199.5 mg/L. Therefore, S. koetjape possesses molluscicidal potential which make it a good source of botanical and organic molluscicide.